2022
DOI: 10.1192/bjo.2022.18
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trials of mood stabilisers for people with autism spectrum disorder: systematic review and meta-analysis

Abstract: Background Despite the widespread use of psychotropic medications in people with autism spectrum disorder (ASD), there is limited evidence to suggest that psychotropic medications including mood stabilisers are effective in individuals with ASD. Aims To carry out a systematic review and meta-analysis of randomised controlled trials (RCTs) that assessed the effectiveness of mood stabilisers in people with ASD. Method We searched the following databases: Cochrane Library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…We also hand-searched four relevant journals in the field of ASD (Autism, Journal of Autism and Developmental Disorders, Autism Research, Journal of Autism Spectrum Disorder) and six in psychopharmacology (Psychopharmacology, Neuropsychopharmacology, International Journal of Neuropsychopharmacology, Journal of Clinical Psychopharmacology, Human Psychopharmacology, Journal of Child and Adolescent Psychopharmacology) for relevant articles between 2000 and 30th May 2022. Search terms using descriptors for ASD, antipsychotics, outcomes (ASD core symptoms, associated symptoms such as challenging behaviour and psychiatric disorders such as psychoses, schizophrenia and mania) and RCTs (online Supplementary Appendix 2) were developed after a scoping search and based on our previous systematic reviews on psychotropic medications in ASD (Deb et al, 2021; Limbu et al, 2022). Two authors (MR and JS) independently screened titles, abstracts and full papers using the eligibility criteria (online Supplementary Appendix 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also hand-searched four relevant journals in the field of ASD (Autism, Journal of Autism and Developmental Disorders, Autism Research, Journal of Autism Spectrum Disorder) and six in psychopharmacology (Psychopharmacology, Neuropsychopharmacology, International Journal of Neuropsychopharmacology, Journal of Clinical Psychopharmacology, Human Psychopharmacology, Journal of Child and Adolescent Psychopharmacology) for relevant articles between 2000 and 30th May 2022. Search terms using descriptors for ASD, antipsychotics, outcomes (ASD core symptoms, associated symptoms such as challenging behaviour and psychiatric disorders such as psychoses, schizophrenia and mania) and RCTs (online Supplementary Appendix 2) were developed after a scoping search and based on our previous systematic reviews on psychotropic medications in ASD (Deb et al, 2021; Limbu et al, 2022). Two authors (MR and JS) independently screened titles, abstracts and full papers using the eligibility criteria (online Supplementary Appendix 2).…”
Section: Methodsmentioning
confidence: 99%
“…Recent meta-analyses showed no definitive evidence of antidepressants, anti-anxiety medication (Deb et al, 2021), and mood stabiliser medications’ efficacy (Limbu et al, 2022) on the core (such as restrictive and repetitive behaviour, RRB and impaired communication skills) or associated symptoms (such as aggression, irritability and agitation) of ASD. The evidence for the efficacy of antipsychotic medications for people with ASD without a psychiatric diagnosis is unclear (Deb et al, 2022; Unwin & Deb, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis (Limbu 2022) found eight RCTs (four on valproate, two on levetiracetam and one each on lamotrigine and topiramate) involving 310 people with ASD, primarily children, that assessed the efficacy of mood stabilisers on core ASD symptoms and associated behaviours, including irritability and aggression but not bipolar disorder. Only two small studies (25%) from the same research group (Hollander 2006(Hollander , 2010 showed superiority of divalproex sodium over placebo.…”
Section: Children With Asdmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) defines a group of heterogenous neurodevelopmental conditions characterized by persistent deficits in social communication and interaction, repetitive and restricted behaviors, and sensory anomalies [1] In the last few decades, numerous pharmacological treatments for these core symptoms of ASD have been investigated, with the majority failing to demonstrate higher efficacy when compared to placebo, in part due to a relatively high placebo response [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%